Climate change and the sustainable use of medicinal plants: a call for “new” research strategies - Mykhailenko, Olha; Jalil, Banaz; McGaw, Lyndy J.; Echeverría, Javier; Takubessi, Marce; Heinrich, Michael (Frontiers in Pharmacology, 2025)
Climate change and human activities severely impact the viability of plants and ecosystems, threatening the environment, biodiversity, and the sustainable development of plant-based products. Biotic and abiotic (ecosystem) determinants affect species distribution and long-term survival, which in turn influence the quality of plants used as herbal medicines and other high-value products. In recent decades, diverse anthropogenic impacts have significantly affected these quality aspects. Climate change, excessive plant exploitation, habitat loss, species vulnerability, and other factors have adversely affected the growth, reproduction, and adaptation of species populations, as well as the quality and volume of primary plant materials supplied to pharmaceutical markets. Despite these growing challenges, there is limited knowledge of potential strategies to prevent or mitigate these impacts, particularly for vulnerable species collected from the wild or harvested from traditional production systems. Hence, effective strategies for preserving and increasing plant populations are urgently needed. In this study, we propose a new framework including the main sustainability factors to better understand and address the vulnerability of a species, hence mitigate the impact of climate change. We assess the applicability of our proposed framework via seven case studies of vulnerable species (i.e., Aquilaria malaccensis Lam., Boswellia sacra Flück., Crocus sativus L., Panax quinquefolius L., Pilocarpus microphyllus Stapf ex Wardlew., Rhodiola rosea L., and Warburgia salutaris (G.Bertol.) Chiov.) from main biogeographic realms, all widely used as medicinal plants. These species present various challenges related to the sustainability of their use, impacting their current and future status locally and globally. Their economic importance, combined with rising demands and specific risks of overexploitation, are also key factors considered here. The suggested framework for the sustainability of medicinal and other high-value plant-based products in the phytopharmaceutical industry emphasises strategies that promote conservation and sustainable resource use. It can also be adapted for other vulnerable species requiring urgent attention.